Specific Intermolecular Interactions of Element-Organic Compounds - Baev, Alexei K. (Springer, 2015)
The nonstereotypical ideas concerning the participation of the carbon pentacoordinated atom in the formation of the specific intermolecular interaction with significantly undivided 2s2(с) electron pairs of carbon atoms (DAl ! CH3– Al ¼ 44.2 kJ mol 1) have been substantiated and the phenomenon of the intramo lecular reverse dative bond between carbon atoms of the methyl group of alkyl ligand and the contacting central molecule atom (in the year 1995) led to the grounded refusal from the model of sp3 hybridization of carbon atoms, proved by the quantum chemical calculations of the methyl compounds of group IV elements. The fourth nonstereotyped idea grounded in the author’s works in the period 1969– 1972 is in classifying the phase transformations to the chemical processes. The values of enthalpies and entropies of the processes are connected to the number and energies of the bursting specific intermolecular interactions. The theory of alterna tive character and the necessity of its further development led to the formulation of the grounding of different types of hydrogen bonds and specific intermolecular interactions, and also to the methodology of the thermodynamic calculation of their energies, building on the vaporization enthalpies applicable for all series of organic compounds.